2017
DOI: 10.1111/ijn.12513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acupressure on pain in Iranian leukemia patients: A randomized controlled trial study

Abstract: Nonpharmacological methods of pain relief such as acupressure are becoming increasingly popular worldwide. Practitioners often claim that such methods are highly effective and less invasive than analgesic drugs, but available empirical evidence is largely inconclusive. This study aimed to test the hypothesis that, postacupressure intervention, the amount of pain experienced by sampled leukemia patients, who received acupressure in addition to standard care, will reduce substantially compared to patients who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 26 publications
1
35
1
Order By: Relevance
“…In this regard, Raddadi et al (2017) concluded that pressure massage of LI4 and BL32 points reduce the pain of patients when intramuscular injection of penicillin compared to the control group [ 26 ]. Contrary to the results of this study, Sharif Nia et al (2017) did not observe a significant difference in the level of pain of leukemia patients during sampling between the two groups of massage therapy and control after 12 sessions of intervention [ 27 ], also, study Ramezani et al (2016) entitled acupressure at point LI4 has not been effective in reducing pain after cesarean section [ 22 ]. One of the reasons for the difference between the results of these studies and our study is the type of disease or the point of massage.…”
Section: Discussioncontrasting
confidence: 74%
“…In this regard, Raddadi et al (2017) concluded that pressure massage of LI4 and BL32 points reduce the pain of patients when intramuscular injection of penicillin compared to the control group [ 26 ]. Contrary to the results of this study, Sharif Nia et al (2017) did not observe a significant difference in the level of pain of leukemia patients during sampling between the two groups of massage therapy and control after 12 sessions of intervention [ 27 ], also, study Ramezani et al (2016) entitled acupressure at point LI4 has not been effective in reducing pain after cesarean section [ 22 ]. One of the reasons for the difference between the results of these studies and our study is the type of disease or the point of massage.…”
Section: Discussioncontrasting
confidence: 74%
“…VAS is a quick, simple, stable, and valid tool that has been used in many investigations and medical trials (Mohseni Bandpei et al 2012). The validity and reliability of this instrument have also been confirmed in previous studies (Hojjati et al 2012;Sharif Nia et al 2017). Patients' oral pain were assessed by the researcher in the first, 7 th and 14 th days using a flashlight, tongue blade, and swaps; a checklist of stomatitis severity and oral pain intensity was also completed.…”
Section: Data Collectionsupporting
confidence: 54%
“…More specifically, these peptides influence the body’s sympatho-adrenal system in such a way that they would result in reduction of pain and anxiety. 21 In the present study, it was determined that acupressure significantly decreased the pain level of the patients in the intervention group. No negative effect was observed during this application.…”
Section: Discussionmentioning
confidence: 60%